The Role of the Financial Services Authority (OJK) in Regulating and Supervising the Health Level of Banks : Peran Otoritas Jasa Keuangan (OJK) Dalam Mengatur dan Mengawasi Tingkat Kesehatan Bank - Ningsih, Ayup Suran; Prasaja, Regina Celiadi; Maharani, Ferra Tiara; Puspa Wardhani, Harumsari (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
In carrying out its business activities, a bank must pay attention to various things considered necessary for the community and the institutions tasked with supervising them, namely maintaining their health. Unhealthy banks cannot carry out good operations and can revoke their business permits. Therefore, the health of a bank is considered very important because it is a driving factor for people to be able to entrust their funds to a bank that can guarantee the security and comfort of people who are customers of that bank. Apart from bank business, the OJK, as a supervisory institution, supervises and ensures that a bank is in a healthy condition and that the bank experiences minimal problems that could put it in a dangerous situation when carrying out its business. Bank obligations and the role of the OJK will be based on Law no. 4 of 2023, which amends Law no. 7 of 1992 and Law no. 10 of 1998 related to banking so that it can maximize the effectiveness of banks in carrying out their obligations to maintain the health of the bank as well as the role of the OJK in supervising and ensuring the health condition of the bank. The writing method that the author applies in writing this article is a normative juridical method, which will focus on implementing or implementing existing and applicable laws and regulations. The result that can be concluded is that we can assess the level of bank health by a series of obligations that the bank must submit to the OJK, as well as the OJK's role, which has been maximized in supervising and assisting banks to maintain health by standards.